The Influence of the European Union Funds on the Development of the Electronic Business Sector in Poland - Czajkowski, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2012)
The article presents the analysis of the results of research concerning the influence of the European Union funds from the Operational Programme Innovative Economy (“PO IG – Program Operacyjny Innowacyjna Gospodarka” in Polish), measure 8.2. supporting B2B in electronic economy and measure 8.1. supporting economic activity in the range of electronic economy (eServices), on the development of the electronic business sector in Poland. Such important aspects as the innovativeness and competitiveness of the surveyed companies and their cooperation with the Implementing Institution – Polish Agency for Entrepreneurship Development (PARP – Polska Agencja Rozwoju Przedsiębiorczości in Polish) are covered. The conclusions from the research and the recommendations concerning the improvements for the future work and cooperation of the Implementing Institution of the financial support with the enterprises are also presented.